Fungsi Bahasa dalam Interaksi Masyarakat Beragam Budaya - Rowimatul Hazizah; Sarah Eya Pepalemsa Br Ginting; Sry Eninta Br Bangun; Welia C Sigalingging; Anggia Puteri (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This research focuses on the exploration of Jakobson's six language functions in social interaction of multicultural society. Different cultural backgrounds often lead to potential misunderstandings, so it is necessary to understand language functions in maintaining communication effectiveness. The purpose of this study is to describe how Jakobson's language functions play a role in strengthening social relations and creating cross-cultural harmony. The research used descriptive qualitative method with literature study approach. Data sources were obtained from books, journals, and related scientific articles, collected through documentation, and analyzed using content analysis techniques with validation through source triangulation. The results showed that the six language functions-referential, emotive, poetic, phatic, conative, and metalingual-do not stand alone, but complement each other in daily communication. In conclusion, language functions have a strategic role as a technical means as well as a social instrument to strengthen cohesion and solidarity in a multicultural society.